Observation and nursing of a patient with constipation of damp-heat type treatment by acupoint massage (经穴推拿治疗1例湿热型便秘患者的护理) - WANG Yali (王亚丽); WEI Yongchun (魏永春); E Haiyan (鄂海燕); TANG Ling (唐玲); DONG Yuxia (董玉霞); QIN Shasha (秦沙沙) (Journal of International Translational Medicine Limited, 2022)
This paper summarized the observation and nursing of a patient with constipation of damp-heat type treatment by acupoint massage. Under the guidance of Traditional Chinese Medicine (TCM) syndrome differentiation and nursing theory, palm massage, one-finger Zen massage, kneading, massage and other meridian massage interventions were carried out. The Traditional Chinese Medicine nursing technology is potentially effective to relieve the constipation nd improve the patient's constitution and their satisfaction with TCM nursing. (本文回顾经穴推拿治疗1例湿热型便秘患者行的效果, 总结相关护理经验。针对湿热型便秘患者, 在中医辨证施护理论指导下, 运用掌摩法、一指禅推法、揉法、推法等经穴推拿治疗进行中医护理, 不仅治愈患者便秘, 同时有效改善患者湿热体质, 提高了患者对中医护理的满意度。)